PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PENDEKATAN SAINTIFIK PADA MATERI BANGUN DATAR UNTUK SISWA KELAS IV SD NEGERI 5 LUBUKLINGGAU - Feni Malinda; Dodik Mulyono; Armi Yuneti (Primary Education Journal Silampari (PEJS), 2021)
This research aims to produce interactive Multimedia-based scientific approaches on the flat wake-up material for students from class IV SD Negeri 5 Lubuklinggau. This research is research and development using 4-D model which consists of 4 stages namely: Define, Design, Development, and Disseminate. This research data collection technique is based on the results of the assessment by the three experts, namely: material experts, media experts, and linguists demonstrate that Multimedia Interactive adhere to valid criteria with an average score of 3.3. At the practicability stage of a small group test consisted of 9 students acquired that Multimedia Interactive criteria with an average score of 3.01. Based on the results of the study can conclude that the interactive multimedia design based on the scientific approach developed in this study proved to be valid and practical towards students in Class 4 SD Negeri 5 Lubuklinggau. Keywords: Multimedia Interkatif, Pendekatan Saintifik, Bangun